2020
DOI: 10.1002/ps.6101
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent development models describing the effects of temperature on the development of Spodoptera eridania

Abstract: BACKGROUND The southern armyworm, Spodoptera eridania, is a polyphagous species native to the American tropics that recently invaded Africa. Knowledge of the impact of temperature on its development and survival is important to understand the risks of this species spreading to other regions and to develop phenological models for pest management. This study evaluated the effects of temperature on the development and survival of S. eridania and selected mathematical models to simulate its development. RESULTS Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 58 publications
4
14
0
3
Order By: Relevance
“…The tropical mountain system in eastern Africa and subtropical humid forests in the Americas, eastern Asia and Australia are also shown to be suitable for SAW. These findings are supported by previous studies on the species ecology which demonstrated the occurrence of the pest in the American tropics 43,44 . In southern Europe, subtropical dry forests can be particularly suitable for S. eridania with a changing climate condition (RCP6.0 and 8.5).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The tropical mountain system in eastern Africa and subtropical humid forests in the Americas, eastern Asia and Australia are also shown to be suitable for SAW. These findings are supported by previous studies on the species ecology which demonstrated the occurrence of the pest in the American tropics 43,44 . In southern Europe, subtropical dry forests can be particularly suitable for S. eridania with a changing climate condition (RCP6.0 and 8.5).…”
Section: Discussionsupporting
confidence: 86%
“…These findings are supported by previous studies on the species ecology which demonstrated the occurrence of the pest in the American tropics. 43 , 44 In southern Europe, subtropical dry forests can be particularly suitable for S. eridania with a changing climate condition (RCP6.0 and 8.5). The total P10 unsuitability of the Benin Republic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The development duration at the six constant temperatures was analyzed using the Kruskal-Wallis test (p < 0.05). Dunn's test was used to compare treatments when the differences were statistically significant (p < 0.05) [9]. The survival of FAWs at egg, larval, and pupal stages was compared among temperatures using a proportion test [32].…”
Section: Effect Of Temperature On the Fitness Of S Frugiperdamentioning
confidence: 99%
“…In contrast, others estimated only T H and T opt (β type and Logan-6) or only T L (linear). The model performance was evaluated using the goodness-of-fit as a statistical criterion and the ability of a single model to correctly estimate temperature thresholds as an additional criterion [9,43,44]. The R square of the regression (R 2 ) was used to evaluate the model's goodness-of-fit.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation